Quality Improvement Project to Improve Adherence to Best Practices to Decrease Incidence of Necrotizing Enterocolitis in Preterm Infants - Ahreen Allana; Sidra Bashir; Ivan Hand (Children)
Background/Objectives: Necrotizing enterocolitis (NEC) is one of the most devastating gastrointestinal emergencies in preterm infants. This quality improvement (QI) project aimed to increase the utilization of accepted evidence-based practices in our neonatal intensive care unit (NICU) to ultimately decrease the incidence of NEC in our level III NICU. Methods: Our QI team implemented a bundle of nine of these evidenced-based practices for NEC prevention and disseminated information among the NICU team. Items in the bundle included delayed cord clamping, parental education on the importance of breast milk, obtaining early consent for donor breast milk, adherence to the unit’s feeding protocol, avoiding routine gastric residual checks, the discontinuation of antibiotics at 48 h once blood cultures were negative, restricting the use of antacids, nasogastric tube (NGT) replacement every 72 h and the removal of central lines once a feeding volume of 100 mL/kg/day was attained. The baseline incidence of clinically proven NEC was found to be 7% at the start of the intervention. We conducted two Plan-Do-Study-Act (PDSA) cycles over a 2-year period from 1 January 2021 to 31 December 2022. Results: There were 74 infants who met the inclusion criteria of being <1500 g and/or at <32 weeks of gestation. The adherence to our process measures improved over the course of our two PDSA cycles from 78% adherence to 91.6%, p < 0.05. The incidence of NEC decreased from 7% to 5.3% following the first PDSA cycle, a 24% reduction. Following the second PDSA cycle, the incidence decreased even further from 5.3% to 2.8%, a 60% reduction from baseline, although this was not statistically significant due to the small sample size. Conclusions: In this QI initiative, we achieved improved adherence to several evidence-based interventions over a two-year period with the aim of reducing the incidence of NEC at our institution.